High-strength basalt fiber composite polyester tire and preparation method thereof

By using components such as epoxy silane coupling agent and epoxidized rubber in basalt fiber composite polyester tires, the problem of insufficient interface bonding force between the fiber and the matrix is ​​solved, the interface strength is improved and the layering phenomenon is prevented, and the toughness and impact resistance of the material are enhanced.

CN119613924APending Publication Date: 2025-03-14YUNNAN XINCHENG WATERPROOF TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411802524.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the harsh environment of high temperature and humidity, the interface bonding between the fiber and the matrix is ​​limited, which can easily lead to stratification.

Method used

By treating the epoxy silane coupling agent on the surface of the fiber, and adding epoxidized rubber, end carboxylic polybutadiene and other components to the matrix, a stable chemical bond and esterification reaction is formed to enhance the interface bonding strength.

Benefits of technology

It significantly improves the interface bonding strength between the fiber and the matrix, prevents the occurrence of layering, and improves the toughness and impact resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613924A_ABST
    Figure CN119613924A_ABST
Patent Text Reader

Abstract

The invention relates to the field of basalt fiber composite polyester tires and discloses a high-strength basalt fiber composite polyester tire and a preparation method thereof.The high-strength basalt fiber composite polyester tire is prepared from, by mass, 40-60 parts of basalt fiber, 55-70 parts of polyester matrix, 13-20 parts of epoxidized rubber, 8-10 parts of carboxyl-terminated polybutadiene, 7-12 parts of bifunctional compound and 8-15 parts of epoxy silane coupling agent. The material is prepared from the following components in parts by weight: 10-15 parts of maleic anhydride grafted polyacrylic acid, 0.5-3 parts of nano silicon dioxide, 0.5-1 part of an antioxidant, 0.4-1 part of an ultraviolet light absorber and 1.7-5 parts of a flame retardant. An active epoxy group is provided through an epoxy silane coupling agent, then carboxyl in a maleic anhydride grafted polymer and the epoxy group are subjected to a ring-opening reaction, stable chemical bonds are formed between fibers and a matrix, the interface bonding strength is remarkably improved, stability can be kept for a long time, and layering is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of basalt fiber composite polyester tires, in particular to a high-strength basalt fiber composite polyester tire and a preparation method thereof. Background Art

[0002] High-strength basalt fiber composite polyester tire is a new type of composite material with excellent performance, mainly composed of basalt fiber and polyester matrix. This material is widely favored for its outstanding high-strength characteristics, good wear resistance and excellent weather resistance. As a high-performance fiber material, basalt fiber has good mechanical properties and corrosion resistance, and can provide strong structural support for composite materials; the polyester matrix gives the material higher toughness and ductility. Therefore, this high-strength composite material has been widely used in infrastructure fields such as buildings, bridges, and tunnels. It is especially suitable for scenes with high requirements for material strength and durability, and can meet the needs of long-term use and the need to withstand harsh environments.

[0003] The traditional production method of basalt fiber composite polyester tire is mainly to simply mix basalt fiber with polyester matrix and then heat it to form. This method relies on the interfacial adhesion between the fiber and the matrix, and does not form a chemical bond, which makes the interfacial bonding force limited. In practical applications, especially in harsh environments such as high temperature and humidity, the interfacial bonding is difficult to withstand stress for a long time, which easily leads to the occurrence of delamination. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a high-strength basalt fiber composite polyester tire and a preparation method thereof, which solves the problem in the prior art that after simple mixing and heating and molding, the interface bonding force between the fiber and the matrix is ​​limited, which easily leads to delamination.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-strength basalt fiber composite polyester tire, comprising the following components in proportion by mass:

[0006] Basalt fiber 40-60 parts

[0007] Polyester matrix 55-70 parts

[0008] Epoxidized rubber 13-20 parts

[0009] Carboxyl-terminated polybutadiene: 8-10 parts

[0010] 7-12 parts of bifunctional compound

[0011] Epoxy silane coupling agent 8-15 parts

[0012] Maleic anhydride grafted polyacrylic acid 10-15 parts

[0013] Nano silicon dioxide 0.5-3 parts

[0014] Antioxidant 0.5-1 part

[0015] 0.4 to 1 part of UV absorber

[0016] 1.7 to 5 parts of flame retardant.

[0017] Preferably, the ultraviolet absorber is 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chloro-2H-benzotriazole absorber, and the bifunctional compound is diglycidyl adipate.

[0018] Preferably, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0019] Preferably, the flame retardant is ammonium polyphosphate.

[0020] A method for preparing a high-strength basalt fiber composite polyester tire comprises the following steps:

[0021] a. Prepare coupling agent solution:

[0022] Select an epoxy silane coupling agent, add it to the ethanol solution and stir it evenly to form a treatment solution for use;

[0023] b. Fiber processing:

[0024] The basalt fiber is immersed in the treatment solution prepared in step a, and after the immersion, the basalt fiber is taken out and dried to cure the epoxy silane coupling agent, so as to obtain the surface-treated basalt fiber for standby use;

[0025] c. Mixing of matrix components:

[0026] Firstly, a polyester matrix is ​​added into a stirrer, and then, after starting the stirrer, epoxidized rubber, carboxyl-terminated polybutadiene, a bifunctional compound and maleic anhydride-grafted polyacrylic acid are added, and the mixture is stirred evenly to form a modified matrix mixture;

[0027] d. Add functional additives:

[0028] After completing step c, add nano silicon dioxide, antioxidant, ultraviolet absorber and flame retardant, keep stirring at the same speed, and cool after stirring to obtain high-strength basalt fiber composite polyester tire;

[0029] e. Composite preparation:

[0030] The basalt fiber treated in step b is gradually added to the functional modified matrix mixture in step d for mixing and stirring, and after stirring and cooling, a high-strength basalt fiber composite polyester is obtained;

[0031] Preferably, in step a, the ethanol solution uses an anhydrous ethanol solution, and the volume ratio of the epoxy silane coupling agent to the anhydrous ethanol solution is: 1-2:8-10.

[0032] Preferably, in the step b, the basalt fiber is immersed in the treatment solution at a temperature of 20 to 25° C. for 30 to 45 minutes, and then taken out and dried at a temperature of 60 to 80° C. for 1 to 2 hours.

[0033] Preferably, in step c, the stirring speed is 400-500 r / min, the temperature is 60-80° C., and the stirring time is 20-30 min.

[0034] Preferably, in step d, the stirring speed and temperature are the same as those in step c, and the stirring time is continued for 15 to 20 minutes.

[0035] Preferably, in step e, the mixing and stirring is performed using a high shear mixer at a rotation speed of 600 to 700 r / min and a temperature of 70 to 90° C. for 15 to 25 min.

[0036] The present invention provides a high-strength basalt fiber composite polyester tire and a preparation method thereof. It has the following beneficial effects:

[0037] 1. The present invention provides active epoxy groups through epoxy silane coupling agents, and then the carboxyl groups in the maleic anhydride grafted polymer undergo a ring-opening reaction with the epoxy groups to form a stable chemical bond between the fiber and the matrix, significantly improving the interface bonding strength, thereby helping to maintain long-term stability and preventing the occurrence of stratification.

[0038] 2. The present invention forms a stable covalent bond through the esterification reaction between the epoxidized rubber and the terminal carboxyl polybutadiene, so that the two can be tightly combined. The epoxidized rubber itself has a certain elasticity. Therefore, after the two are combined, the elastic molecules inside can undergo elastic deformation when impacted, thereby effectively absorbing the impact energy and improving the toughness of the final product. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Please see attached Figure 1 ,

[0042] A high-strength basalt fiber composite polyester tire, comprising the following components in proportion by mass:

[0043] Basalt fiber 40-60 parts

[0044] Polyester matrix 55-70 parts

[0045] Epoxidized rubber 13-20 parts

[0046] Carboxyl-terminated polybutadiene: 8-10 parts

[0047] 7-12 parts of bifunctional compound

[0048] Epoxy silane coupling agent 8-15 parts

[0049] Maleic anhydride grafted polyacrylic acid 10-15 parts

[0050] Nano silicon dioxide 0.5-3 parts

[0051] Antioxidant 0.5-1 part

[0052] 0.4 to 1 part of UV absorber

[0053] 1.7 to 5 parts of flame retardant.

[0054] The ultraviolet absorber is 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chloro-2H-benzotriazole absorber, and the bifunctional compound is diglycidyl adipate.

[0055] By using 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chloro-2H-benzotriazole absorber, since it is a very effective ultraviolet absorber, it can effectively absorb the UV-A and UV-B bands in the ultraviolet rays, and the ultraviolet rays in these two bands have a great influence on the aging of the material, so it can avoid the high-energy ultraviolet rays from directly acting on the base material, thereby delaying the photodegradation process of the material, and it has good thermal stability and chemical inertness, good compatibility with polyester base materials, can be evenly distributed in the polyester base, and is not easy to migrate, thereby ensuring the uniformity and durability of the ultraviolet protection effect; and by using diglycidyl adipate as a bifunctional compound, its cross-linked network can be used to close the microporous structure on the surface of the material, which has a barrier effect on the penetration of external chemicals and improves the material's resistance to chemical corrosion. At the same time, diglycidyl adipate has a low shrinkage rate during the curing and cross-linking process, which helps to avoid stress concentration inside the material, is conducive to maintaining good dimensional stability, and improves the molding accuracy and surface finish of the product.

[0056] The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0057] Since pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] has a large molecular weight, it has low mobility and can stay in the polyester matrix for a long time, providing a lasting antioxidant effect. At the same time, low mobility also reduces the risk of antioxidant loss over time, thereby ensuring that the composite material still has good anti-aging properties in long-term applications.

[0058] The flame retardant is ammonium polyphosphate.

[0059] Since ammonium polyphosphate is a highly efficient flame retardant containing phosphorus and nitrogen, it can release phosphoric acid and ammonia when heated. These components can suppress flames at high temperatures. Phosphoric acid will form a protective carbon layer on the surface of the material, isolating oxygen and effectively preventing the spread of flames. At the same time, the gases generated by ammonium polyphosphate during combustion are mainly water vapor and nitrogen, and no toxic smoke will be produced, which reduces pollution to the environment and ensures the safety of the material during combustion.

[0060] A method for preparing a high-strength basalt fiber composite polyester tire comprises the following steps:

[0061] a. Prepare coupling agent solution:

[0062] Select an epoxy silane coupling agent, add it to the ethanol solution and stir it evenly to form a treatment solution for use;

[0063] b. Fiber processing:

[0064] The basalt fiber is immersed in the treatment solution prepared in step a, and after the immersion, the basalt fiber is taken out and dried to cure the epoxy silane coupling agent, so as to obtain the surface-treated basalt fiber for standby use;

[0065] c. Mixing of matrix components:

[0066] Firstly, a polyester matrix is ​​added into a stirrer, and then, after starting the stirrer, epoxidized rubber, carboxyl-terminated polybutadiene, a bifunctional compound and maleic anhydride-grafted polyacrylic acid are added, and the mixture is stirred evenly to form a modified matrix mixture;

[0067] d. Add functional additives:

[0068] After completing step c, add nano silicon dioxide, antioxidant, ultraviolet absorber and flame retardant, keep stirring at the same speed, and cool after stirring to obtain high-strength basalt fiber composite polyester tire;

[0069] e. Composite preparation:

[0070] The basalt fiber treated in step b is gradually added to the functional modified matrix mixture in step d for mixing and stirring, and after stirring and cooling, a high-strength basalt fiber composite polyester is obtained;

[0071] Preferably, in step a, the ethanol solution uses an anhydrous ethanol solution, and the volume ratio of the epoxy silane coupling agent to the anhydrous ethanol solution is: 1-2:8-10.

[0072] Preferably, in step b, the basalt fiber is immersed in the treatment solution at a temperature of 20 to 25° C. for 30 to 45 minutes, taken out and dried at 60 to 80° C. for 1 to 2 hours.

[0073] Preferably, in step c, the stirring speed is 400-500 r / min, the temperature is 60-80° C., and the stirring time is 20-30 min.

[0074] Preferably, in step d, the stirring speed and temperature are the same as those in step c, and the stirring time is continued for 15 to 20 minutes.

[0075] Preferably, in step e, the mixing and stirring is carried out using a high shear mixer at a speed of 600 to 700 r / min and a temperature of 70 to 90° C. for 15 to 25 min.

[0076] Embodiment 1:

[0077] Objective: To explore the effect of epoxy silane coupling agent and maleic anhydride grafted polymer content on the interfacial strength of the high-strength basalt fiber composite polyester tire obtained in the present invention.

[0078] Experimental Group 1

[0079] Group distribution ratio:

[0080] Basalt fiber: 50 parts

[0081] Polyester matrix: 65 parts

[0082] Epoxidized rubber: 15 parts

[0083] Carboxyl-terminated polybutadiene: 9 parts

[0084] Bifunctional compounds: 10 parts

[0085] Epoxy silane coupling agent: 10 parts

[0086] Maleic anhydride grafted polymer: 12 parts

[0087] Nano silicon dioxide: 1.5 parts

[0088] Antioxidant: 1 part

[0089] Ultraviolet absorber: 0.8 parts

[0090] Flame retardant: 3 parts

[0091] Preparation steps:

[0092] Preparation of coupling agent solution: Mix epoxy silane coupling agent with anhydrous ethanol in a volume ratio of 1:8 and stir evenly.

[0093] Fiber treatment: The basalt fiber was immersed in the coupling agent solution at 25°C for 45 minutes, and then dried at 80°C for 2 hours.

[0094] Mixing of matrix components: Add polyester matrix, epoxidized rubber, carboxyl-terminated polybutadiene, bifunctional compound and maleic anhydride grafted polymer into a stirrer in sequence and stir at 70°C for 25 minutes.

[0095] Add functional additives: Add nano-silica, antioxidant, UV absorber and flame retardant, and continue stirring for 20 minutes.

[0096] Composite preparation: The treated basalt fiber was gradually added into the matrix, and stirred with a high shear mixer at 80°C and a rotation speed of 650 r / min for 20 minutes to obtain a high-strength basalt fiber composite polyester tire.

[0097] Experimental Group 2

[0098] Group distribution ratio:

[0099] Epoxy silane coupling agent: 16 parts

[0100] Maleic anhydride grafted polymer: 16 parts

[0101] The remaining components were the same as those in Experimental Group 1. Preparation steps: The same as those in Experimental Group 1.

[0102] Experimental Group 3

[0103] Group distribution ratio:

[0104] Epoxy silane coupling agent: 6 parts

[0105] Maleic anhydride grafted polymer: 6 parts

[0106] The remaining components were the same as those in Experimental Group 1. Preparation steps: The same as those in Experimental Group 1.

[0107] Experimental Group 4

[0108] Group distribution ratio:

[0109] Epoxy silane coupling agent: 10 parts

[0110] Maleic anhydride grafted polymer: 16 parts

[0111] The remaining components were the same as those in Experimental Group 1. Preparation steps: The same as those in Experimental Group 1.

[0112] Experimental Group 5

[0113] Group distribution ratio:

[0114] Epoxy silane coupling agent: 10 parts Maleic anhydride grafted polymer: 9 parts (below the range of 10-15) The remaining components are the same as those in Experimental Group 1 Preparation steps: The same as the preparation steps of Experimental Group 1.

[0115] Experimental Group 6

[0116] Group distribution ratio:

[0117] Epoxy silane coupling agent: 16 parts

[0118] Maleic anhydride grafted polymer: 12 parts

[0119] The remaining components were the same as those in Experimental Group 1.

[0120] Preparation steps: Same as those of experimental group 1.

[0121] Experimental Group 7

[0122] Group distribution ratio:

[0123] Epoxy silane coupling agent: 6 parts

[0124] Maleic anhydride grafted polymer: 12 parts

[0125] The remaining components were the same as those in Experimental Group 1.

[0126] Preparation steps: Same as those of experimental group 1.

[0127] Test experiment

[0128] Experimental purpose: To test and compare the interfacial strength of the final products prepared in each experimental group, so as to evaluate the effects of different contents of epoxy silane coupling agent and maleic anhydride grafted polymer on the interfacial strength.

[0129] Experimental steps:

[0130] The composite material samples prepared in each experimental group were taken and the interface strength was tested using an electronic tensile testing machine.

[0131] Test conditions: The sample was stretched at a speed of 50 mm / min, and the interfacial strength of each sample at the time of tensile fracture was recorded.

[0132] Each experimental group was tested 3 times and the average value was taken for comparison

[0133] The comparative experimental data are shown in Table 1.

[0134] Table 1: Component analysis comparison data table

[0135]

[0136]

[0137] Data analysis and summary

[0138] Comparison between experimental group 1 and experimental group 2: The content of epoxy silane coupling agent and maleic anhydride grafted polymer in experimental group 2 was higher than the recommended range, and the interface strength was reduced to 110MPa, 15MPa lower than that of experimental group 1 (125MPa). The data show that excessive coupling agent and maleic anhydride grafted polymer content may lead to excessive saturation of the interface layer between the fiber and the matrix, thereby weakening the interface strength and even generating a brittle layer, affecting the overall bonding and strength of the material.

[0139] Comparison between experimental group 1 and experimental group 3: The content of epoxy silane coupling agent and maleic anhydride grafted polymer in experimental group 3 was lower than the recommended range, and the interface strength dropped to 100MPa, 25MPa lower than that of experimental group 1. This result shows that insufficient content of coupling agent and grafted polymer will lead to insufficient bonding between fiber and matrix, weakening the interface strength. The right amount of coupling agent and grafted polymer is crucial to enhancing interface adhesion.

[0140] Comparison between experimental group 1 and experimental group 4: the epoxy silane coupling agent in experimental group 4 was within the recommended range, while the content of maleic anhydride grafted polymer was higher than the recommended range, and the interface strength was 115 MPa, 10 MPa lower than that of experimental group 1. This shows that when the content of maleic anhydride grafted polymer is too high, although the effect of the coupling agent is maintained, the excessive grafted polymer may produce a relatively fragile interface layer, resulting in a decrease in interface strength.

[0141] Comparison between experimental group 1 and experimental group 5: The epoxy silane coupling agent in experimental group 5 was within the recommended range, but the content of maleic anhydride grafted polymer was lower than the recommended range, and the interface strength was 118 MPa, 7 MPa lower than that of experimental group 1. Although the appropriate amount of coupling agent was maintained, the lack of grafted polymer reduced the chemical bonding force between the fiber and the matrix, resulting in a slight decrease in interface strength.

[0142] Comparison between experimental group 1 and experimental group 6: the content of epoxy silane coupling agent in experimental group 6 was higher than the recommended range, while the maleic anhydride grafted polymer was within the recommended range, and the interface strength was 112 MPa, 13 MPa lower than that of experimental group 1. This result shows that despite the reasonable proportion of grafted polymer, excessive coupling agent may still cause unnecessary brittleness in the interface layer, thereby reducing the overall strength.

[0143] Comparison between experimental group 1 and experimental group 7: The epoxy silane coupling agent content of experimental group 7 is lower than the recommended range, while the maleic anhydride grafted polymer is within the recommended range, and the interface strength is 108MPa, 17MPa lower than that of experimental group 1. This result once again proves the importance of an appropriate amount of coupling agent to maintain a strong interface bond between the fiber and the matrix. When the coupling agent is insufficient, the interface strength will decrease significantly.

[0144] Summarize

[0145] From the above data comparison, it can be seen that the interface strength of experimental group 1 (epoxysilane coupling agent and maleic anhydride grafted polymer are both within the recommended range) is the highest, at 125MPa, which is significantly better than other experimental groups. The appropriate amount of epoxysilane coupling agent and maleic anhydride grafted polymer can form a stable and high-strength bond in the interface layer, so that the interface strength of the fiber and the polyester matrix is ​​optimal. This result verifies the superiority of the ingredient ratio in the formula of the present invention in improving the interface strength, and is the best choice for the application of high-strength composite materials.

[0146] Embodiment 2

[0147] Objective: To explore the effect of epoxidized rubber and carboxyl-terminated polybutadiene content on the toughness of the high-strength basalt fiber composite polyester tire obtained in the present invention.

[0148] Experimental Group 8

[0149] Group ratio: The ratio of experimental group 1 in Example 1 is used, that is,

[0150] Basalt fiber: 50 parts

[0151] Polyester matrix: 65 parts

[0152] Epoxidized rubber: 15 parts

[0153] Carboxyl-terminated polybutadiene: 9 parts

[0154] Bifunctional compounds: 10 parts

[0155] Epoxy silane coupling agent: 10 parts

[0156] Maleic anhydride grafted polymer: 12 parts

[0157] Nano silicon dioxide: 1.5 parts

[0158] Antioxidant: 1 part

[0159] Ultraviolet absorber: 0.8 parts

[0160] Flame retardant: 3 parts

[0161] Preparation steps: The same as the preparation steps of experimental group 1 in Example 1, that is,

[0162] Preparation of coupling agent solution: Mix epoxy silane coupling agent with anhydrous ethanol in a volume ratio of 1:8 and stir evenly.

[0163] Fiber treatment: The basalt fiber was immersed in the coupling agent solution at 25°C for 45 minutes, and then dried at 80°C for 2 hours.

[0164] Mixing of matrix components: Add polyester matrix, epoxidized rubber, carboxyl-terminated polybutadiene, bifunctional compound and maleic anhydride grafted polymer into a stirrer in sequence and stir at 70°C for 25 minutes.

[0165] Add functional additives: Add nano-silica, antioxidant, UV absorber and flame retardant, and continue stirring for 20 minutes.

[0166] Composite preparation: The treated basalt fiber was gradually added into the matrix, and stirred with a high shear mixer at 80°C and a rotation speed of 650 r / min for 20 minutes to obtain a high-strength basalt fiber composite polyester tire.

[0167] Experimental Group 9

[0168] Group distribution ratio:

[0169] Epoxidized rubber: 21 parts

[0170] Carboxyl-terminated polybutadiene: 11 parts

[0171] The remaining components were the same as those in Experimental Group 8.

[0172] Preparation steps: Same as those of experimental group 8.

[0173] Experimental Group 10

[0174] Group distribution ratio:

[0175] Epoxidized rubber: 12 parts

[0176] Carboxyl-terminated polybutadiene: 7 parts

[0177] The remaining components were the same as those in Experimental Group 8.

[0178] Preparation steps: Same as those of experimental group 8.

[0179] Experimental Group 11

[0180] Group distribution ratio:

[0181] Epoxidized rubber: 15 parts Carboxyl-terminated polybutadiene: 11 parts The remaining components are the same as those in Experimental Group 8.

[0182] Preparation steps: Same as those of experimental group 8.

[0183] Experimental Group 12

[0184] Group distribution ratio:

[0185] Epoxidized rubber: 15 parts Carboxyl-terminated polybutadiene: 7 parts The remaining components are the same as those in Experimental Group 8.

[0186] Preparation steps: Same as those of experimental group 8.

[0187] Experimental Group 13

[0188] Group distribution ratio:

[0189] Epoxidized rubber: 21 parts Carboxyl-terminated polybutadiene: 9 parts The remaining components are the same as those in Experimental Group 8.

[0190] Preparation steps: Same as those of experimental group 8.

[0191] Experimental Group 14

[0192] Group distribution ratio:

[0193] Epoxidized rubber: 12 parts Carboxyl-terminated polybutadiene: 9 parts The remaining components are the same as those in Experimental Group 8.

[0194] Preparation steps: Same as those of experimental group 8.

[0195] Test experiment

[0196] Experimental purpose: To test and compare the toughness of the final products prepared in each experimental group, so as to evaluate the effect of different contents of epoxidized rubber and carboxyl-terminated polybutadiene on the toughness of the composite material.

[0197] Experimental steps:

[0198] The composite material samples prepared in each experimental group were taken and the toughness was tested using an impact testing machine.

[0199] Test conditions: Apply standardized impact force to the sample and record the impact strength (kJ / m 2 ).

[0200] Each experimental group was tested 3 times and the average value was taken for comparison.

[0201] The comparative experimental data are shown in Table 2.

[0202] Table 2: Component analysis comparison data table

[0203] Experimental Group Epoxidized rubber (parts) Carboxyl-terminated polybutadiene (parts) <![CDATA[Impact strength (kJ / m 2 ) <!-- 8 -->]]> Experimental Group 8 15 9 52 Experimental Group 9 21 11 46 Experimental Group 10 12 7 41 Experimental Group 11 15 11 50 Experimental Group 12 15 7 48 Experimental Group 13 21 9 49 Experimental Group 14 12 9 44

[0204] Data analysis and summary

[0205] Comparison between experimental group 8 and experimental group 9: The epoxidized rubber and carboxyl-terminated polybutadiene in experimental group 9 are both above the recommended range, and the impact strength is reduced to 46 kJ / m2, which is 6 kJ / m2 lower than that of experimental group 8 (52 kJ / m2). The data show that excessive rubber and polybutadiene content will cause the material to deform more under high impact loads, thereby reducing the overall toughness.

[0206] Comparison between experimental group 8 and experimental group 10: The epoxidized rubber and carboxyl-terminated polybutadiene in experimental group 10 were both below the recommended range, and the impact strength dropped to 41 kJ / m2, 11 kJ / m2 lower than that of experimental group 8. This shows that the low content of epoxidized rubber and carboxyl-terminated polybutadiene weakened the flexibility of the material, making it difficult to absorb enough energy under impact.

[0207] Comparison between experimental group 8 and experimental group 11: The epoxidized rubber of experimental group 11 is within the recommended range, while the carboxyl-terminated polybutadiene is above the range, and the impact strength is 50 kJ / m2, which is 2 kJ / m2 lower than that of experimental group 8. This result shows that when the carboxyl-terminated polybutadiene is slightly higher, it has less effect on toughness, but too high a content will increase the brittleness of the interface.

[0208] Comparison between experimental group 8 and experimental group 12: The epoxidized rubber of experimental group 12 is within the recommended range, while the carboxyl-terminated polybutadiene is below the range, and the impact strength is 48 kJ / m2, which is 4 kJ / m2 lower than that of experimental group 8. The lack of carboxyl-terminated polybutadiene weakens the impact resistance of the material, resulting in a slight decrease in toughness.

[0209] Comparison between experimental group 8 and experimental group 13: The epoxidized rubber of experimental group 13 is higher than the recommended range, while the carboxyl-terminated polybutadiene is within the recommended range. The impact strength is 49 kJ / m2, which is 3 kJ / m2 lower than that of experimental group 8. 2 This indicates that excessive epoxidized rubber may increase flexibility, causing the material to deform more under impact, thereby reducing the overall toughness.

[0210] Comparison between experimental group 8 and experimental group 14: The epoxidized rubber of experimental group 14 is below the recommended range, while the carboxyl-terminated polybutadiene is within the recommended range. The impact strength is 44 kJ / m2, which is 8 kJ / m2 lower than that of experimental group 8. 2 The lower epoxidized rubber content makes it difficult for the material to form a strong interface layer, thereby reducing the overall toughness.

[0211] Summarize

[0212] From the data comparison, it can be seen that the impact strength of experimental group 8 (epoxidized rubber and carboxyl-terminated polybutadiene are both within the recommended range) reaches 52kJ / m2, which is the best toughness among all experimental groups, verifying the significant effect of appropriate amounts of epoxidized rubber and carboxyl-terminated polybutadiene on improving the toughness of composite materials. The appropriate content balances the flexibility and impact resistance of the material, making it more suitable for application scenarios with high toughness requirements.

[0213] Summary Analysis

[0214] Comparison results between Example 1 and Example 2

[0215] In Example 1, the effects of the content of epoxy silane coupling agent and maleic anhydride grafted polymer on the interface strength of the composite material were investigated; in Example 2, the effects of the content of epoxidized rubber and terminal carboxyl polybutadiene on the toughness of the composite material were investigated.

[0216] Since the composition ratio and preparation steps of Experimental Group 8 in Example 2 are exactly the same as those of Experimental Group 1 in Example 1, Experimental Group 8 and Experimental Group 1 are the same experimental groups, and both of them perform best in terms of interface strength and toughness, showing the advantages of the present invention. The following is a detailed comparative analysis:

[0217] Comparison results of experimental group 1 with other experimental groups

[0218] 1. Interface Strength Comparison (Results of Example 1)

[0219] Experimental group 1 performed best in terms of interface strength (125MPa), and the interface strength of other experimental groups decreased due to the deviation of the content of epoxysilane coupling agent and maleic anhydride grafted polymer from the recommended range. By comparing with experimental group 1, it can be seen that when the content of coupling agent and grafted polymer is higher or lower than the recommended range (such as experimental groups 2, 3, 4, 5, 6, 7), the interface strength is lower than that of experimental group 1.

[0220] Therefore, experimental group 1 has the best interfacial strength, indicating that the ratio of coupling agent and grafted polymer in an appropriate range is more conducive to the improvement of interfacial bonding strength.

[0221] 2. Toughness comparison (results of Example 2)

[0222] Experimental group 8 (i.e., experimental group 1) also showed the best impact strength (52 kJ / m 2 ), the toughness performance of each group is as follows: when the content of epoxidized rubber and terminal carboxyl polybutadiene is higher or lower than the recommended range (such as experimental groups 9, 10, 11, 12, 13, and 14), the impact strength of the material is lower than that of experimental group 8,

[0223] Therefore, the toughness of experimental group 8 is the best, which verifies that the appropriate amount of epoxidized rubber and terminal carboxyl polybutadiene can optimize the flexibility and impact resistance of the material.

[0224] Summary of the advantages of experimental group 1

[0225] Experimental Group 1 (i.e., Experimental Group 8) showed the best results in both performance tests, proving the advantages of the formula of the present invention: in terms of interface strength, the content of epoxysilane coupling agent and maleic anhydride grafted polymer in Experimental Group 1 was within an appropriate range, forming a strong interface bond, significantly improving the interface strength of the material. In terms of toughness, the content of epoxidized rubber and carboxyl-terminated polybutadiene in Experimental Group 1 (i.e., Experimental Group 8) was moderate, so that the composite material had good flexibility and high impact resistance.

[0226] In summary, experimental group 1 (i.e., experimental group 8) is significantly better than other experimental groups in both key properties, verifying the superiority of epoxysilane coupling agent, maleic anhydride grafted polymer, epoxidized rubber, and carboxyl-terminated polybutadiene in the formula of the present invention within the recommended range. This ratio formula is conducive to the balance of high interfacial strength and high toughness, making it suitable for a variety of composite material application scenarios requiring high strength and durability.

[0227] Comparative Experimental Design

[0228] Purpose:

[0229] 1. Verify the effect of epoxy silane coupling agent and maleic anhydride grafted polymer on the interfacial strength of high-strength basalt fiber composite polyester tire.

[0230] 2. Verify the effect of epoxidized rubber and carboxyl-terminated polybutadiene on the toughness of high-strength basalt fiber composite polyester tires.

[0231] Experimental design:

[0232] Experimental group 1 (i.e., experimental group 8) was compared with the following control group (conventional high-strength basalt fiber composite polyester tire):

[0233] Control group 1 (traditional high-strength basalt fiber composite polyester tire A): no epoxy silane coupling agent

[0234] Control group 2 (conventional high-strength basalt fiber composite polyester tire B): no maleic anhydride grafted polymer

[0235] Control group 3 (traditional high-strength basalt fiber composite polyester tire C): no epoxy silane coupling agent and maleic anhydride grafted polymer

[0236] Control group 4 (conventional high-strength basalt fiber composite polyester tire D): no epoxidized rubber

[0237] Control group 5 (traditional high-strength basalt fiber composite polyester tire E): terminal carboxyl polybutadiene

[0238] Control group 6 (conventional high-strength basalt fiber composite polyester tire F): no epoxidized rubber and carboxyl-terminated polybutadiene

[0239] Experimental procedures

[0240] Sample preparation:

[0241] Composite samples were prepared according to the formula of experimental group 1 and each control group. For the control group, the corresponding components were removed from the composition, but the other components and proportions were the same as those of experimental group 1.

[0242] Preparation process:

[0243] Preparation of coupling agent solution: For the group containing epoxysilane coupling agent, the coupling agent was mixed with anhydrous ethanol at a volume ratio of 1:8 and stirred evenly.

[0244] Fiber treatment: basalt fiber was immersed in coupling agent solution (this step was omitted for the control group without coupling agent) at 25°C for 45 minutes, and then taken out and dried at 80°C for 2 hours.

[0245] Mixing of matrix components: Add polyester matrix, then add epoxidized rubber (omit this step for the control group without epoxidized rubber), terminal carboxyl polybutadiene (omit this step for the control group without terminal carboxyl polybutadiene), bifunctional compound and maleic anhydride grafted polymer (omit this step for the control group without maleic anhydride grafted polymer), and stir for 25 minutes.

[0246] Add functional additives: Add nano-silica, antioxidant, UV absorber and flame retardant, and continue stirring for 20 minutes.

[0247] Composite preparation: The treated basalt fibers were gradually added to the matrix mixture, stirred with a high shear mixer at 80°C and a rotation speed of 650 r / min for 20 minutes, and then cooled.

[0248] Performance Test:

[0249] Interface strength test: Use an electronic tensile testing machine to test the interface strength of the samples, and record the interface strength (MPa) of each sample at tensile fracture.

[0250] Toughness test: Use an impact testing machine to test the impact strength of the sample and record the impact strength (kJ / m 2 ).

[0251] Test conditions

[0252] Interface strength test speed: 50mm / min.

[0253] Each group was tested 3 times and the average value was taken.

[0254] Impact testing applies a standardized impact force to the sample and records the impact strength when it breaks.

[0255] The comparative experimental data are shown in Table 3.

[0256] Table 3: Component analysis comparison data table

[0257]

[0258] Data analysis and summary of the advantages of experimental group 1

[0259] Comparison between experimental group 1 and control group 1 (A):

[0260] Interface strength: The experimental group 1 is 13MPa higher than the control group 1 (125MPa vs. 112MPa). This indicates that the epoxy silane coupling agent helps to improve the bonding force between the fiber and the matrix and increases the interface strength.

[0261] Toughness: The impact strength of experimental group 1 is slightly higher than that of control group 1 (52 kJ / m2 vs. 50 kJ / m2), indicating that the epoxy silane coupling agent also has a certain promoting effect on toughness.

[0262] Comparison between experimental group 1 and control group 2 (B):

[0263] Interface strength: The experimental group 1 was 10 MPa higher than the control group 2, which proved the importance of maleic anhydride grafted polymer in enhancing interface strength.

[0264] Toughness: The impact strength of experimental group 1 is 3kJ / m2 higher than that of control group 2 (52kJ / m2 vs. 49kJ / m 2 ), indicating that maleic anhydride grafted polymer is also helpful in improving toughness.

[0265] Comparison between experimental group 1 and control group 3 (C):

[0266] Interface strength: Experimental group 1 is 20 MPa higher (125 MPa vs. 105 MPa), indicating the combined effect of epoxy silane coupling agent and maleic anhydride grafted polymer on interface strength.

[0267] Toughness: The impact strength of experimental group 1 is 5 kJ / m2 higher (52 kJ / m2 vs. 47 kJ / m2), proving that the two ingredients have a synergistic effect on improving toughness.

[0268] Comparison between experimental group 1 and control group 4 (D):

[0269] Interface strength: The interface strength of experimental group 1 is 7 MPa higher than that of control group 4 (125 MPa vs. 118 MPa).

[0270] Toughness: The impact strength of experimental group 1 is 7 kJ / m2 higher than that of control group 4 (52 kJ / m2 vs. 45 kJ / m 2 ), the epoxidized rubber has a significant effect on improving toughness.

[0271] Comparison between experimental group 1 and control group 5 (E):

[0272] Interface strength: Experimental group 1 is 5MPa higher than control group 5 (125MPa vs. 120MPa).

[0273] Toughness: Experimental group 1 is 6 kJ / m2 higher than control group 5 (52 kJ / m2 vs. 46 kJ / m2), indicating that the carboxyl-terminated polybutadiene has a good contribution to toughness.

[0274] Comparison between experimental group 1 and control group 6 (F):

[0275] Interface strength: Experimental group 1 is 15MPa higher (125MPa vs. 110MPa), proving that the combined effect of epoxidized rubber and carboxyl-terminated polybutadiene has a positive effect on interface strength.

[0276] Toughness: The experimental group 1 is 10 kJ / m2 higher than the control group 6 (52 kJ / m2 vs. 42 kJ / m2), indicating that the epoxidized rubber and the carboxyl-terminated polybutadiene have a significant effect on improving the toughness of the composite material.

[0277] Summary of the advantages of experimental group 1

[0278] Experimental group 1 demonstrates comprehensive advantages in interface strength and toughness through reasonable proportions:

[0279] Interface strength: The combination of epoxysilane coupling agent and maleic anhydride grafted polymer in experimental group 1 significantly improves the interface strength, showing a good bonding effect between the fiber and the matrix. Toughness: The appropriate application of epoxidized rubber and carboxyl-terminated polybutadiene makes the material have higher flexibility and impact resistance under impact conditions, showing the best toughness data. Overall, experimental group 1 is significantly better than each control group, verifying the superiority of the present invention in balancing interface strength and toughness, and is suitable for application in the field of composite materials with high strength and high toughness requirements.

[0280] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength basalt fiber composite polyester tire, characterized in that: Includes the following components in groups by mass: Basalt fiber 40-60 parts Polyester matrix 55-70 parts Epoxidized rubber 13-20 parts Carboxyl-terminated polybutadiene: 8-10 parts 7-12 parts of bifunctional compound Epoxy silane coupling agent 8-15 parts Maleic anhydride grafted polyacrylic acid 10-15 parts Nano silicon dioxide 0.5-3 parts Antioxidant 0.5-1 part 0.4-1 part of UV absorber 1.7 to 5 parts of flame retardant.

2. The high-strength basalt fiber composite polyester tire according to claim 1, characterized in that: The ultraviolet absorber is 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chloro-2H-benzotriazole absorber, and the bifunctional compound is diglycidyl adipate.

3. The high-strength basalt fiber composite polyester tire according to claim 1, characterized in that: The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

4. The high-strength basalt fiber composite polyester tire according to claim 1, characterized in that: The flame retardant is ammonium polyphosphate.

5. A method for preparing a high-strength basalt fiber composite polyester tire, used for preparing a high-strength basalt fiber composite polyester tire as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: a. Prepare coupling agent solution: Select an epoxy silane coupling agent, add it to the ethanol solution and stir it evenly to form a treatment solution for use; b. Fiber processing: The basalt fiber is immersed in the treatment solution prepared in step a, and after the immersion, the basalt fiber is taken out and dried to cure the epoxy silane coupling agent, so as to obtain the surface-treated basalt fiber for standby use; c. Mixing of matrix components: Firstly, a polyester matrix is ​​added into a stirrer, and then, after starting the stirrer, epoxidized rubber, carboxyl-terminated polybutadiene, a bifunctional compound and maleic anhydride-grafted polyacrylic acid are added, and the mixture is stirred evenly to form a modified matrix mixture; d. Add functional additives: After completing step c, add nano silicon dioxide, antioxidant, ultraviolet absorber and flame retardant, keep stirring at the same speed to form a functional modified matrix mixture; e. Composite preparation: The basalt fibers treated in step b are gradually added to the functionally modified matrix mixture in step d for mixing and stirring, and after stirring and cooling, a high-strength basalt fiber composite polyester is obtained.

6. The method for preparing a high-strength basalt fiber composite polyester tire according to claim 5, characterized in that: In the step a, the ethanol solution uses an anhydrous ethanol solution, and the volume ratio of the epoxy silane coupling agent to the anhydrous ethanol solution is: 1-2:8-10.

7. The method for preparing a high-strength basalt fiber composite polyester tire according to claim 5, characterized in that: In the step b, the basalt fiber is immersed in the treatment solution at a temperature of 20 to 25° C. for 30 to 45 minutes, and then taken out and dried at a temperature of 60 to 80° C. for 1 to 2 hours.

8. The method for preparing a high-strength basalt fiber composite polyester tire according to claim 5, characterized in that: In the step c, the stirring speed is 400-500 r / min, the temperature is 60-80° C., and the stirring time is 20-30 min.

9. The method for preparing a high-strength basalt fiber composite polyester tire according to claim 5, characterized in that: In step d, the stirring speed and temperature are the same as those in step c, and the stirring time is continued for 15 to 20 minutes.

10. The method for preparing a high-strength basalt fiber composite polyester tire according to claim 5, characterized in that: In the step e, the mixing and stirring is performed using a high shear mixer at a rotation speed of 600 to 700 r / min and a temperature of 70 to 90° C. for 15 to 25 minutes.

Citation Information

Cited By

  • High-strength corrosion-resistant polyester base fabric

    CN121519261A